SYSTEM OF TRANSPORTATION OF ORDERS BY AIR TRANSPORT UNITS (DRONES)IN A DYNAMIC NETWORK - MIKHALEVSKYI, V.; SKRYPNYK, T.; TYMCHUK, MARIA (Herald of Khmelnytskyi National University. Technical sciences, 2024)
The article proposes an approach to the transportation of orders by air transport units (drones) in a dynamic network. The issue of using drones as transport units in the logistics sector is becoming more important every year. The growth of technology forces various types of enterprises and organizations to engage in the use of modern information and technical support in order to meet the needs of their enterprise and compete with their opponents. Therefore, one of the next steps in transport logistics may be the use of drones and accompanying software for their management. The idea of ​​implementing air delivery of orders is currently only at the stage of formation and its successful application depends on a list of factors, one of which is the use of software for optimal system operation. The principle of operation is as follows: the company provides an open API service for creating a delivery request both by an ordinary user through an application, website or physical branch, and for entrepreneurs and companies to integrate the API with their service. The logistics system assumes the presence of centers, where each has a certain number of vehicles (drones), their current unit ready for work, maximum and involved in the work quantity. The direction of practical use of the developed method and tools is the automation of the selection of the optimal order delivery route in a dynamic network based on cloud technologies.